Evaluation of the suicide registration system in Maputo and Matola, Mozambique, 2016-2018 - Eduardo Mangue Chicanequisso; Ivandra Magaia; Virgílio Ceia Francisco; Érika Valeska Rossetto; Cynthia Sema Baltazar (Journal of Interventional Epidemiology and Public Health)
Introduction: Suicide is a major public health problem worldwide and a major cause of death in young adults. Mozambique had one the highest suicide rate in Africa with 23.2 suicides per 100 000 inhabitants. We aimed to evaluate the Suicide Registration System in the cities of Maputo and Matola (SRSMM) to have an overview of the system and to assess the suicide burden in the population.